Reflexivity : the essential guide - May, Tim, 1957-; Perry, Beth (London : SAGE Publications Ltd, 2017)
Reflexivity-the critical examination of how we see the world-is integral to good research practice. From this state-of-the-art, accessible tour of its history and contemporary relevance, readers will learn of its importance to social research and to society generally. The text introduces a host of influential thinkers and their key ideas on reflexivity, and incorporates examples from a range of disciplines and research settings. Drawing on the authors' extensive experience of real research settings, this book: . Pinpoints the importance of reflexivity in social research . Demonstrates its relevance to everyday life . Firmly locates the concept in the history of ideas . Explores key questions about the bases of knowledge and understanding . Presents key thinkers, concepts and issues in easy-to-understand learning boxes The result is a book that provides students and researchers in the social sciences with the knowledge and understanding necessary not only to examine the role of reflexivity in contemporary life, but to apply it in their own research practice.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social sciences -- Research; Social sciences -- Methodology; Reflection (Philosophy)